2001
DOI: 10.1029/2001gl013531
|View full text |Cite
|
Sign up to set email alerts
|

Snowpack photochemical production of HONO: A major source of OH in the Arctic boundary layer in springtime

Abstract: Abstract. Both snow manipulation experiments and ambient measurements during the Polar Sunrise Experiment 2000 atAlert (Alert2000) indicate intensive photochemical production of nitrous acid (HONO) in the snowpack. This process constitutes a major HONO source for the overlying atmospheric boundary layer in the Arctic during the springtime, and sustained concentrations of HONO high enough that upon photolysis they became the dominant hydroxyl radical (OH) source. This implies a much greater role for OH radicals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
298
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(321 citation statements)
references
References 13 publications
(8 reference statements)
22
298
1
Order By: Relevance
“…At the relative humidity of !40% observed during the measurement intensive, there should be at least several monolayers of water on the glass manifold wall surfaces [Svensson et al, 1987;Saliba et al, 2001]. Thus the produced NO 2(ads) may react rapidly with adsorbed H 2 O to produce HONO, which is then released from the surface into the air [Pitts et al, 1984] This mechanism is consistent with the recent observations of photochemical production of HONO [Zhou et al, 2001] and NO x [Honrath et al, 1999[Honrath et al, , 2000 in snowpack from nitrate/HNO 3 photolysis. These observations are also supportive of a recent hypothesis that the photolysis of adsorbed HNO 3 /nitrate on ground surfaces is a major daytime source of HONO and thus is responsible for the observed elevated HONO concentrations in the rural atmospheric boundary layer .…”
Section: Resultssupporting
confidence: 77%
“…At the relative humidity of !40% observed during the measurement intensive, there should be at least several monolayers of water on the glass manifold wall surfaces [Svensson et al, 1987;Saliba et al, 2001]. Thus the produced NO 2(ads) may react rapidly with adsorbed H 2 O to produce HONO, which is then released from the surface into the air [Pitts et al, 1984] This mechanism is consistent with the recent observations of photochemical production of HONO [Zhou et al, 2001] and NO x [Honrath et al, 1999[Honrath et al, , 2000 in snowpack from nitrate/HNO 3 photolysis. These observations are also supportive of a recent hypothesis that the photolysis of adsorbed HNO 3 /nitrate on ground surfaces is a major daytime source of HONO and thus is responsible for the observed elevated HONO concentrations in the rural atmospheric boundary layer .…”
Section: Resultssupporting
confidence: 77%
“…[36][37][38][39][40][41][42][43] While the night time formation of HONO in the atmosphere is reasonably well explained by direct emissions and different heterogeneous conversion processes of NO 2 [44][45][46] on ground surfaces, 42 recent sensitive measurements have shown unexpectedly high HONO concentrations during the daytime. 36,38,41,43,47 The measured HONO levels were significantly higher than the values predicted on the basis of the available knowledge about daytime sources and sinks of HONO. The experiments revealed the existence of a strong daytime source of HONO up to 60 times higher than the night time sources 43 and contributing up to 60% to the direct OH radical sources, 48 which was suggested to arise from the photolysis of adsorbed HNO 3 /nitrate 38,47,[49][50][51] or by heterogeneous photochemistry of NO 2 on organic substrates.…”
Section: ð1þmentioning
confidence: 82%
“…36,38,41,43,47 The measured HONO levels were significantly higher than the values predicted on the basis of the available knowledge about daytime sources and sinks of HONO. The experiments revealed the existence of a strong daytime source of HONO up to 60 times higher than the night time sources 43 and contributing up to 60% to the direct OH radical sources, 48 which was suggested to arise from the photolysis of adsorbed HNO 3 /nitrate 38,47,[49][50][51] or by heterogeneous photochemistry of NO 2 on organic substrates. [52][53][54] Recent work in our laboratory on different aspects of aromatic hydrocarbon photooxidation processes performed in the presence of OH-radical scavengers has revealed that OH radicals are generated during the photolysis of nitrophenols.…”
Section: ð1þmentioning
confidence: 82%
“…This includes different surfaces (ground and aerosols) such as the photocatalytic conversion of NO 2 on mineral dust (Ndour et al 2008), the dark heterogeneous conversion of NO 2 on suspended soot particles (Ammann et al 1998;Arens et al 2001), the heterogeneous hydrolysis of NO 2 (Finlayson-Pitts et al 2003), the photosensitized reduction of NO 2 on organic surfaces (George et al 2005;Stemmler et al 2006), the photolysis of adsorbed nitric acid (HNO 3 ) (Zhou et al 2003) and nitrate (NO 3 − ) (Zhou et al 2001), the HNO 3 conversion on primary organic aerosols (Ziemba et al 2010) and from soilemitted nitrite (Su et al 2011). Direct emissions from combustion processes (i.e.…”
Section: Responsible Editor: Gerhard Lammelmentioning
confidence: 99%